Genome-Wide Association Study Detected Novel Susceptibility Genes for Schizophrenia and Shared Trans-Populations/Diseases Genetic Effect. (3rd October 2018) - Ikeda, Masashi; Takahashi, Atsushi; Kamatani, Yoichiro; Momozawa, Yukihide; Saito, Takeo; Kondo, Kenji; Shimasaki, Ayu; Kawase, Kohei; Sakusabe, Takaya; Iwayama, Yoshimi; Toyota, Tomoko; Wakuda, Tomoyasu; et al.
Abstract: Genome-wide association studies (GWASs) have identified >100 susceptibility loci for schizophrenia (SCZ) and demonstrated that SCZ is a polygenic disorder determined by numerous genetic variants but with small effect size. We conducted a GWAS in the Japanese (JPN) population (a) to detect novel SCZ-susceptibility genes and (b) to examine the shared genetic risk of SCZ across (East Asian [EAS] and European [EUR]) populations and/or that of trans-diseases (SCZ, bipolar disorder [BD], and major depressive disorder [MDD]) within EAS and between EAS and EUR (trans-diseases/populations). Among the discovery GWAS subjects (JPN-SCZ GWAS: 1940 SCZ cases and 7408 controls) and replication dataset (4071 SCZ cases and 54479 controls), both comprising JPN populations, 3 novel susceptibility loci for SCZ were identified: SPHKAP ( P best = 4.1 × 10 −10 ), SLC38A3 ( P best = 5.7 × 10 −10 ), and CABP1 - ACADS ( P best = 9.8 × 10 −9 ). Subsequent meta-analysis between our samples and those of the Psychiatric GWAS Consortium (PGC; EUR samples) and another study detected 12 additional susceptibility loci. Polygenic risk score (PRS) prediction revealed a shared genetic risk of SCZ across populations ( P best = 4.0 × 10 −11 ) and between SCZ and BD in the JPN population ( P 10 −40 ); however, a lower variance-explained was noted between JPN-SCZ GWAS and PGC-BD or MDD within/across populations. Genetic correlation analysis supported the PRS results; the genetic correlation between JPN-SCZ and PGC-SCZ was ρ = 0.58, whereas a similar/lower correlation was observed between the trans-diseases (JPN-SCZ vs JPN-BD/EAS-MDD, r g = 0.56/0.29) or trans-diseases/populations (JPN-SCZ vs PGC-BD/MDD, ρ = 0.38/0.12). In conclusion, (a) Fifteen novel loci are possible susceptibility genes for SCZ and (b) SCZ "risk" effect is shared with other psychiatric disorders even across populations.